Depression among teachers: a Swedish register-based study - Erika Johansson; Daniel Falkstedt; Melody Almroth (BMC, 2022)
Abstract Background Some studies have suggested that teachers are particularly at risk for mental health problems but the research in this area has not been conclusive. This study aims to compare the risk of being diagnosed with depression for different types of teachers in Sweden, both with each other and with the rest of the population, using register data. Methods Just over 3 million individuals age 30-60 were included of which 256,166 were teachers. The exposure variable was the occupation held in 2005 and the outcome was any diagnosis of depression during the follow up period of 2006 to 2016. The data was analyzed using Cox proportional hazard regression. Results Around 5 % of women and 3 % of men developed depression during the follow up. For women, teachers had a decreased risk of developing depression compared to non-teachers, but this association was no longer present after adjusting for common covariates including education. For men, teachers had an increased risk of depression both before and after adjustment (HR 1.27 95% CI 1.22-1.32). When comparing different kinds of teachers to university teachers, several types of teachers including primary and special education teachers had an increased risk among men while primary and secondary teachers had a decreased risk among women. Conclusion The increased risk of depression in male teachers is a result that requires further exploration in terms of occupational differences between male and female teachers.